2014
DOI: 10.1371/journal.pone.0084549
|View full text |Cite|
|
Sign up to set email alerts
|

Sloth Hair as a Novel Source of Fungi with Potent Anti-Parasitic, Anti-Cancer and Anti-Bacterial Bioactivity

Abstract: The extraordinary biological diversity of tropical forests harbors a rich chemical diversity with enormous potential as a source of novel bioactive compounds. Of particular interest are new environments for microbial discovery. Sloths – arboreal mammals commonly found in the lowland forests of Panama – carry a wide variety of micro- and macro-organisms on their coarse outer hair. Here we report for the first time the isolation of diverse and bioactive strains of fungi from sloth hair, and their taxonomic place… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 61 publications
1
32
0
1
Order By: Relevance
“…These species are xenarthran mammals which diverged from other eutherians during the early Cenozoic (Meredith et al 2011), making them only very distantly related to rodents and primates. To our knowledge, there has not been any cancer reported in sloths; however, sloth fur carries an anti-cancer fungus (Higginbotham et al 2014).…”
Section: Discussionmentioning
confidence: 89%
“…These species are xenarthran mammals which diverged from other eutherians during the early Cenozoic (Meredith et al 2011), making them only very distantly related to rodents and primates. To our knowledge, there has not been any cancer reported in sloths; however, sloth fur carries an anti-cancer fungus (Higginbotham et al 2014).…”
Section: Discussionmentioning
confidence: 89%
“…), we built phylogenetic trees for groups of OTUs with similar sequences (1–52 isolates per data set) (as described in Higginbotham et al. , Spear ). Because not all sequences mapped onto named fungal species, we assigned each operational species a unique species code (Appendix : Table S3).…”
Section: Methodsmentioning
confidence: 99%
“…First, we assigned operational taxonomic units (OTUs) by manually editing all reads, automatically assembling bidirectional reads into consensus sequences using a minimum of 20% overlap and 85% sequence similarity, and clustering the 288 consensus sequences and two unidirectional sequences based on a minimum of 40% overlap and 90%, 95%, 97%, and 99% sequence similarity using Sequencher (Gene Codes, Ann Arbor, Michigan, USA). Second, because sequence similarity for the ITS region varies across fungal species (O'Brien et al 2005), we built phylogenetic trees for groups of OTUs with similar sequences (1-52 isolates per data set) (as described in Higginbotham et al 2014, Spear 2017. Because not all sequences mapped onto named fungal species, we assigned each operational species a unique species code (Appendix S1: Table S3).…”
Section: Identifying Fungal Species By Dna Sequencing (Conditions 1a mentioning
confidence: 99%
“…[6,9] An umber of studies have shown ar elationship between cancer and malaria in regard to diagnostics, drug research, treatment, prevention, and epidemiology. [10][11][12][13] Different classes of antimalarial drugs display direct or adjuvant activity against cancer cell lines, are knowna ss ensitivity reversers of resistant tumor cell lines or inhibitors of drug resistance development, or have synergistic action with knowna nticancer drugs. [14][15][16][17][18][19][20] Althought heir exact mode of action against canceri ss till not completely understood,v arious mechanisms have been proposed.…”
Section: Introductionmentioning
confidence: 99%